Development of semi-automated synthesis procedure for radiolabelling of an engineered subtype specific GABAA binding antibody fragment with [18F]AmBF3-Tz - Akbari Samani, Negar (My University, 2023)
The heterogeneity of GABAA receptors, characterized by the diversity in their subunit composition and distribution, is believed to give rise to distinct functional and physiological roles, or pharmacological effects. Changes in GABAAR subtypes and their functions have been linked to neurological and psychiatric disorders. A promising technique for elucidating the roles of GABAAR subtypes in both normal physiology and pathological conditions involves in vivo imaging of GABAARs using positron emission tomography (PET). PET is a medical imaging technique that involves introducing a minute quantity of radioactive molecule, known as a radiotracer, into the body to visualize and measure metabolic and functional processes at the molecular level. However, commonly used radiotracers for imaging GABAARs exhibit binding specificity without subtype selectivity. Consequently, there is an ongoing quest to develop radiotracers that are selectively tailored to specific GABAAR subtypes. Recently, an anti-GABAAR subunit α1 scFv1F4 was developed at the Turku PET Centre. The primary aim of this thesis was to optimize the reaction conditions for the radiolabeling of this antibody fragment. To achieve this, an alkylammoniomethyltrifluoroborate with a tetrazine moiety ([18F]AmBF3-Tz) was used as the prosthetic group. The boron fluoride acceptor in AmBF3-Tz allows for a straightforward one-step radiofluorination via 19F/18F isotope exchange. Additionally, the tetrazine moiety facilitates the chemoselective radiolabeling of TCO-functionalized biomolecules under mild conditions through bioorthogonal IEDDA click reaction. The radiolabeling of AmBF3-Tz via 19F/18F isotope exchange was fast and occurred in aqueous conditions. However, for obtaining [18F]AmBF3-Tz in high radiochemical yields, microliter reaction volumes were required. Consequently, optimization was essential for adapting this radiosynthesis to a conventional radiosynthesis unit. Under optimized conditions, [18F]AmBF3-Tz was produced in high radiochemical purity of 98.6 ± 1.4% and good radiochemical yield of 21.5 ± 1.21%. Following radiosynthesis, [18F]AmBF3-Tz was used for chemoselective radiolabeling of the anti-GABAAR subunit α1 scFv1F4 that was functionalized with trans-cyclooctenes (TCO). Starting from [18F]AmBF3-Tz, the RCY of [18F]scFv1F4-TCO-AmBF3-Tz was 45.9 ± 12.6 % (n = 3), providing radiolabeled fragment with high enough activity and quality (RCP of ≥ 99%) for biological evaluation. The results from the PET studies demonstrate that the anti-GABAAR subunit α1 scFv1F4 can serve as a promising subtype-specific radiotracer for imaging GABAARs. However, at this stage, applications of the radiotracer are limited to the peripheral nervous system, as it cannot cross the blood-brain barrier. In conclusion, a semi-automated radiosynthesis sequence was developed for microliter production of [18F]AmBF3-Tz with good yield and high radiochemical purity. The synthesized [18F]AmBF3-Tz was successfully used for radiolabeling of a TCO-conjugated GABAAR α1 subunit specific scFv1F4 for biological evaluation of the fragment binding in vivo.
Keywords: GABAAR, PET imaging, fluorine-18, organotrifluoroborates